Postharvest biology and technology for preserving fruit quality - Valero, Daniel; Serrano, Maria , 1963- (CRC Press, 2010)
The book chronicles the changes in postharvest technology during the past three decades, highlighting the advances made possible through a deeper understanding of the postharvest physiology of raw produce. It focuses on how to maintain both sensorial and nutritional fruit quality parameters while also extending shelf life. The authors present a wide range of technological applications for postharvest strategies, including heat treatments, naturally-occurring compounds, modified atmosphere packaging, non-toxic chemical compounds, and active packaging. The text also discusses the advantages and disadvantages of using cold temperatures during handling, packaging, and storage. Although each chapter constitutes a separate unit, which could be used in a stand-alone fashion, the order and continuity of the chapters provide a more complete understanding of the subject. Exploring future directions, the book concludes with coverage of emerging technologies such as atmospheres with high O2, biological control, and the use of UV-light. It offers a firm grounding in the basic knowledge of postharvest research, technology, and applications. The text illustrates a broad range of approaches, based on years of research, and brings them together in a convenient, easily accessible resource